Length-Weight Relationship and Condition Factor Channa Marulioides (Bleeker, 1851) In Kapuas River – West Kalimantan as a Conservation Aquatic Resources Effort: Length-Weight Relationship and Condition Factor of Channa marulioides - Hutagalung, Rizal Akbar; Anggoro, Sutrsino; Suryanti, Suryanti; Muskananfola, Max Rudolf (Department of Aquaculture, 2024)
Channa marulioides is one of the species that is facing a population decrease due to high fishing activity. This study aims to determine the value of the length-weight relationship and condition factors of C. marulioides in the Kapuas River as a relevant conservation effort. Several sampling areas in this study were used to represent the Kapuas River, including Kapuas Hulu River in Kapuas Hulu Regency, Putussibau District; The central part of the waters area of